Checklist of Indian Pterostichinae Bonelli, 1810 (Coleoptera: Carabidae). (3rd April 2021) - Manikandan, Divya; Sabu, K. Thomas
ABSTRACT: An up to date checklist of Indian Pterostichinae (Coleoptera: Carabidae) with taxonomic data including type species, literature details and distribution patterns of the 159 species belonging to five tribes namely, \ Abacetini (58 species), Cratocerini (11 species), Morionini (2 species), Pterostichini (52 species) and Zabrini (36 species) are provided. Out of the 159 species, 87 are exclusively Indian and 72 species (excluding the eighty-seven exclusively Indian species) have wider range of geographic distribution. Among 87 exclusively Indian species (54.71%), 46 species (28.9%) are recorded from the Oriental region in India, 32 species (20%) from the Palaearctic and seven species from both Oriental and Palaearctic regions. Sixty species (37.7%) are endemic to the three global hotspots of biodiversity (the Western Ghats and Sri Lanka-12 species; the Himalaya-38 species and the Indo Burma-10 species) in India. First report of Abacetus guttula Chaudoir, 1869 from south India and the erroneous status of exclusively Indian genus Stomonaxellus Tschitscherine, 1901 as a subgenus of Caelostomus MacLeay, 1825 are reported.